PUBLIC POLICIES, PANDEMIC AND CORRUPTION: THE “VACUNAGATE” CASE IN PERU - Tapia, Manuel Bermúdez (Revista Direitos Sociais e Políticas Públicas (UNIFAFIBE), 2025)
In the period from March to October 2021, the presidency of the Republic of Peru under Martín Vizcarra Cornejo had developed a series of public policies that sought to address the Covid-19 pandemic, including a process that involved the search and acquisition of vaccines against the virus that had left the country in a situation of national calamity. Upon leaving the government, preliminary inquiries had determined that the negotiation and acquisition of vaccines involved a series of acts that could generate an alleged commission of crimes, until it was certified that the vaccine inoculation process had been carried out on characters of the direction of government and people linked to the scope of the presidency of the country. As a result of this situation, the situation in Peru is analyzed in a text developed under a qualitative hermeneutical methodology, analyzing the negative impact of the alleged crimes committed during the development of public policy that sought to address the pandemic. , as a study problem. The proposed objective is the evaluation of the constitutional and criminal responsibilities and the formulation of a reform of the State policy in Peru for the attention of emergencies in a state of exception is proposed as a hypothesis.